ANALYSIS OF TOURIST SATISFACTION WITH ATTRACTIONS AND SERVICES IN TOURISM VILLAGES IN NAGARI SUNGAI BATANG, AGAM REGENCY - ibnu, ibnu kuntara; Agustar, Asdi; Fitriana, Widya (Universitas Pancasakti Tegal, 2025)
This research aims to obtain information and insights regarding tourists’ perceptions of the attractiveness of Sungai Batang Tourism Village, which encourage them to visit and return. Additionally, the study seeks to assess tourist satisfaction levels based on four key tourism product attributes: attractions, amenities, accessibility, and ancillary services.The research employs a quantitative method with a survey approach. Data were collected through questionnaires distributed to tourists visiting the village, with a sample size of 50 respondents. The analyzed variables include the quality of tourist attractions, facilities, services, and the overall tourist experience.The results indicate that overall tourist satisfaction is in the